Dissociative identity disorder (did) of marc Spector in marvel cinematic universe’s show ‘moon knight’: a psycholinguistic analysis - Fitria Aprilia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study examines a psychological disorder called dissociative identity disorder (DID) in the Marvel Cinematic Universe’s show Moon Knight, which premiered on March 30, 2022, and ran for six episodes. The aim of this study is to analyze the dissociative identity disorder (DID) that is being experience by Marc Spector, the main character of Marvel Cinematic Universe’s show, Moon Knight. This study has two objectives, (1) To find out what are the causes of dissociative identity disorder on Marc Spector in Marvel Cinematic Universe’s show Moon Knight. (2) To find out clinical features of dissociative identity disorder on Marc Spector in Marvel Cinematic Universe’s show Moon Knight. (3) To find out how dissociative identity disorder affects the way Marc Spector communicates. The method used in this study were qualitative method. The data of this study were obtained from a Marvel Cinematic Universe’s show Moon Knight. The techniques for collecting data were by watching every episode of the show, taking notes, classifying the data, doing interpretation, and drawing conclusion. The result of the analysis reveals Marc Spector is able to talk different accent and different language when he shifted to his alter ego.